1990
DOI: 10.1128/iai.58.5.1384-1390.1990
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumor necrosis factor alpha production by a human immunoglobulin preparation for intravenous use

Abstract: We investigated the effect of a pH 4-treated human immunoglobulin preparation for intravenous use (pH4-G) on the production of tumor necrosis factor alpha (TNF-at) in vivo. The level of TNF-at in the sera of rabbits receiving pH4-G before lipopolysaccharide (LPS) injection was lower than that in rabbits receiving only LPS.Similarly, the in vitro production of TNF-a was suppressed by pH4-G. Rabbit peritoneal exudate cells stimulated with LPS in the presence of pH4-G produced less TNF-a than did those stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 14 publications
0
23
1
Order By: Relevance
“…The authors did not observe an induction and overproduction of any of the inhibitory 'L 1996 Blackwell Science Ltd, Clinical and Experimema/lmmuno/ogy, 104, Suppl. 1: [10][11][12][13][14][15][16][17][18][19][20] cytokincs studied as the cause of the IVIG-mediated suppression. Although the formation of IL-l receptor antagonist or TGF-(J was not assessed, it is unlikely that these cytokines would prevent ionomycin/PMA activation ofT cells, which is a monocyte-independent means of cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not observe an induction and overproduction of any of the inhibitory 'L 1996 Blackwell Science Ltd, Clinical and Experimema/lmmuno/ogy, 104, Suppl. 1: [10][11][12][13][14][15][16][17][18][19][20] cytokincs studied as the cause of the IVIG-mediated suppression. Although the formation of IL-l receptor antagonist or TGF-(J was not assessed, it is unlikely that these cytokines would prevent ionomycin/PMA activation ofT cells, which is a monocyte-independent means of cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Kuhnert and coworkers reported that LPS-stimulated cultured human monocytes were primed to increased IL-l and TNF-c~ synthesis by preincubation with IVIG [12]. The opposite results, in terms of IL-l and TNF-a production, were observed when rabbit macrophages were cocultured with LPS and IVIG [13,14]. In vitro, superantigen stimulation of human-blood T lymphocytes by staphylococcal enterotoxin A (SEA) was inhibited by IVIG.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported previously that homologous IgG suppresses the production of cytokines in vitro from human monocytes and mononuclear cells [24][25][26], but the mechanism of this action has remained unclear. It has further been reported that the production of IL-1a and TNF-a from macrophages (rabbit) stimulated by LPS is also suppressed by addition of heterologous (human) IgG [27,28]. This action is thought to be associated with the Fc region.…”
Section: Groups Activated T Cells Macrophages Activated T Cells Macromentioning
confidence: 95%
“…A decreased production of IL-l has been observed after infusion of IVIG in patients suffering with Kawasaki disease [25] and in rabbits injected with lipopolysaccharide (LPS) that had been pretreated with IVIG (23]. It has been suggested that IVIG suppresses LPS-induccd production of TNF-a and IL-l through an increase in I intracellular levels of cAMP following the interaction of IVIG with Fer receptors on monocytes [26,27]. A marked increase in plasma levels of IL-lra with !000-fold molar excess of IL-lra to IL-l(:J in some patients has been reported in a recent study [28].…”
Section: Modulation Of Synthesis and Release Of Cytokines And Cytokinmentioning
confidence: 99%